Standardization of Seesa Salaka - Surendran, Surya; Sindhu, C (International Research Journal of Ayurveda & Yoga, 2025)
Seesa Salaka Samskarana Vidhi has been well described in Ayurvedic classical texts. The Samanya and Vishesha Sodhita Seesa are subjected to Payana Vidhi for 7 times separately in Triphala kashayam, Bhringa Swarasa, Jala, Go Ghritam, Ajaksheera, and Madhuyashti kashayam. Even though it is told as an instrument it itself acts as a medicine. This can be understood from the following verse “netre yukta sanjana ananjana va,” i.e., it provides the quality of medicine even without anjana. Hence, in this study, an effort has been made for the preparation and standardization of Seesa salaka. The standardization of Seesa Salaka was carried out in four steps. The initial three were done by conducting physicochemical analysis of raw material, Samanya Vishesha Sodhita Seesa, and Payitha Seesa, respectively. Finally, standardization of Seesa salaka has been done as per the dimension criteria mentioned in Ayurvedic classics.